ROS signaling, oxidative stress and Nrf2 in pancreatic beta-cell function - Pi, Jingbo (2009)
This review focuses on the emerging evidence that reactive oxygen species (ROS) derived from glucose metabolism, such as H(2)O(2), act as metabolic signaling molecules for glucose-stimulated insulin secretion (GSIS) in pancreatic beta-cells. Particular emphasis is placed on the potential inhibitory role of endogenous antioxidants, which rise in response to oxidative stress, in glucose-triggered ROS and GSIS. We propose that cellular adaptive response to oxidative stress challenge, such as nuclear factor E2-related factor 2 (Nrf2)-mediated antioxidant induction, plays paradoxical roles in pancreatic beta-cell function. On the one hand, induction of antioxidant enzymes protects beta-cells from oxidative damage and possible cell death, thus minimizing oxidative damage-related impairment of insulin secretion. On the other hand, the induction of antioxidant enzymes by Nrf2 activation blunts glucose-triggered ROS signaling, thus resulting in reduced GSIS. These two premises are potentially relevant to impairment of beta-cells occurring in the late and early stage of Type 2 diabetes, respectively. In addition, we summarized our recent findings that persistent oxidative stress due to absence of uncoupling protein 2 activates cellular adaptive response which is associated with impaired pancreatic beta-cell function.